How Are Pesticides Classified? - Frederick M. Fishel (EDIS)
This guide explains the classification system used by experts to define how pesticides are classified. This document is PI-46, one of a series of the Pesticide Information Office, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date June 2005.